The accuracy of Hopkins Symptom Checklist – 25 (HSCL-25) depression subscales (Indonesian version) on adolescents - Ayu Rahmawati Tirto; Sherly S. Turnip (Humanitas: Indonesian Psychological Journal, 2019)
Hopkins Symptom Checklist - 25 (HSCL-25) depression subscales is an easy-to-use, mainstream screening to detect early stage of depression symptoms, including on adolescents. The accuracy studies of HSCL-25 conducted all over the countries indicated a relatively good accuracy. However, there has been no accuracy testing on HSCL-25 in Indonesia. This study aimed to examine the accuracy of HSCL-25 depression subscales (Indonesian version) by comparing it to semi-structured diagnostic interview as the gold standard. This was a non-experimental study by diagnostic interviewing 40 participants. The results of depression status from the interview then compared to HSCL-25 depression subscales scores from previous study. The results analyzed using crosstabs, pearson chi square, and Receiver Operatic Characteristic (ROC) analysis to obtain the accuracy and the optimum cut-off score. The results show that HSCL-25 depression subscales have a good sensitivity (87.5%) and fairly good specificity (65.4%) with the +LR of 2.5 and –LR of .2. The cut-off score used in this study (1.75) was optimum to be used as a cut-off point in the prevention context. Then it can be conclude that HSCL-25 have a fairly good accuracy and the current cut-off score used was already good for detecting the early depression symptoms among adolescents.